2013
DOI: 10.1080/21658005.2013.832848
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the baculum in the red fox (Vulpes vulpes) from Slovakia

Abstract: Despite a large number of studies on the variability of the baculum (os penis) in several orders of mammals, detailed data about the baculum of Vulpes vulpes are very few. The aim of this study was to investigate the data on quantitative characteristics of the size of the baculum and describe the variability of the baculum of V. vulpes from the transition region between the Eastern and Western Carpathians (Slovakia). The study presents the morphological variation in 10 traits of the baculum based on an analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Similar analysis in this study confirmed that the bacular length was well correlated with head-and-body length. Positive correlations between the bacular dimensions between each other as well with the baculum weight confirmed their relationship to provide mechanical support during copulation and interact more directly with the female reproductive tract (Baryshnikov et al 2003, Čanády 2013, Čanády & Čomor 2013, Ča nády & Onderková 2016a. Reutte et al (2015) proved sexual size dimorphism in favour of males for both species (Martes martes and M. foina) for somatic measures.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar analysis in this study confirmed that the bacular length was well correlated with head-and-body length. Positive correlations between the bacular dimensions between each other as well with the baculum weight confirmed their relationship to provide mechanical support during copulation and interact more directly with the female reproductive tract (Baryshnikov et al 2003, Čanády 2013, Čanády & Čomor 2013, Ča nády & Onderková 2016a. Reutte et al (2015) proved sexual size dimorphism in favour of males for both species (Martes martes and M. foina) for somatic measures.…”
Section: Discussionmentioning
confidence: 87%
“…The bone size served as a reliable indicator of good genes to female mates during breeding (Krawczyk et al 2011). In our previous studies of the baculum in carnivores from Western Carpathians were proved that bacular length was generally less variable than other thickness measurements (Čanády 2013(Čanády , Čanády & Čomor 2013(Čanády , Čanády & Onderková 2016a. This may be due to the ease of measurement (measurement error), because length measurements are basically error-free.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mechanically, than the latter. In addition, it should also be noted that several authors (Malecha, Krawczyk, and Hromada 2009;Schwery et al 2011;Čanády 2013;Čanády and Čomor 2013) confirmed a lower variability in the length of the penis bone and a greater variability in its thickness. These observations together with positive correlations between the measured parts of the baculum can play an important role in increasing the strength of the bone and preventing its possible fracture during copulation.…”
mentioning
confidence: 88%
“…However, Bonduriansky (2007) stated that the interpretations of allometric relationships in the context of sexual selection must be carefully considered. Several data are available on baculum variability in family Canidae (Pohl 1911;Burt 1960;Harrison and Bates 1989;Lariviére and Ferguson 2002;Dixson and Anderson 2004;Gültiken et al 2004;Sharir et al 2011;Čanády 2013;Čanády and Čomor 2013;Lundy 2014). Nevertheless, all previous studies have analysed only variability in baculum size.…”
Section: Introductionmentioning
confidence: 94%